Role of CDK4 as prognostic biomarker in Soft Tissue Sarcoma and synergistic effect of its inhibition in dedifferentiated liposarcoma sequential treatment - Silvia Vanni; Giacomo Miserocchi; Graziana Gallo; Valentina Fausti; Sofia Gabellone; Chiara Liverani; Chiara Spadazzi; Claudia Cocchi; Chiara Calabrese; Giovanni De Luca; Massimo Bassi; Manlio Gessaroli; et al. (Experimental Hematology & Oncology, 2024)
Abstract Soft tissue sarcomas represent an heterogeneous group of rare mesenchymal tumors comprising 1% of all solid malignancies. Among them, liposarcoma is one of the most common histotypes with atypical lipomatous tumor/well differentiated liposarcoma and dedifferentiated liposarcoma (ALT/WDLPS and DDLPS) as the major sub-entities. The unavailability of predictive, prognostic and druggable biomarkers makes the management of these lesions challenging. In recent years CDK4 and its inhibitors have emerged as potential agents for these lesions especially for ALT/WDLPS and DDLPS but the results are not conclusive and need to be elucidated. This study involved 21 ALT/WDLPS and DDLPS patients. Histological analyses of MDM2 and CDK4 were carried out. Moreover, a DDLPS patient-derived cancer model was established in vitro and in vivo assessing the efficacy of palbociclib in combination and sequential treatment. Finally, in silico analyses on CDK4 expression were carried out. The results showed a higher expression of CDK4 and MDM2 in DDLPS compared to ALT/WDLPS. Moreover, no correlation between MDM2 expression and CDK4 was observed. Next, in vitro analysis of CDK4 inhibitor palbociclib showed an antagonistic effect when combined to other chemotherapeutics, while it exhibited a significant synergy when administered in sequential schedule with lenvatinib. Next, in vivo analysis on DDLPS xenotransplanted embryos assessing the efficacy and safety profile of the in vitro tested schedules confirmed the observed data. This proof-of-concept study sheds light on the natural history of ALT/WDLPS and DDLPS and provides the rationale for the clinical applicability of sequential treatment with palbociclib in the management of DDLPS.